Readability of Initial Public Offering Prospectus and Earnings Performance - Shette, Rachappa; Kuntluru, Sudershan (International Journal of Economics and Financial Issues, 2018)
The present study examines the readability of IPO prospectus in relation to short-term earnings performance and long-term earnings surprise. In this study, Fog Index is the measure of IPO prospectus readability. Cross-sectional regression models are applied on 115 IPOs to examine the effect of readability scores on earnings performance and earnings surprise. Based on empirical analysis, we find positive correlation between Fog index and IPO-year earnings performance. In the short-run, IPO-year earnings performance of companies with difficult to read prospectus is higher than that of companies with easy to read prospectus. In the long-run, the earnings surprise for companies with difficult to read prospectus is higher than that of companies with easy to read prospectus. Unlike the existing studies, application of readability index to IPO prospectus and linking it with short-term earnings performance and long-term earnings surprise is the contribution of the study. Keywords: Firm performance, Readability, Initial Public Offerings, IPO, India JEL Classifications: L25, G32, O53